CONSERVATION AREA AT CIREBON QUARRY (MT. BLINDIS) ANDS IT’S POTENCY IN CARBON SEQUESTRATION - Yulistyarini, Titut; Fiqa, Abban Putri; Laksono, Rachmawan Adi (JURNAL BIOLOGI INDONESIA, 2016)
The biodiversity conservation areas of Cirebon quarry, in this case Blindis and Sari mountains is a limestone ecosystem.Limestone ecosystems play an important role in climate regulation. Quantifying the organic carbon storage of limestoneecosystems in this area definitely helps to evaluate the roles of these ecosystems in both global and regional carbon cyclesand also their impact on climate. This research was carried out to know the complete data of carbon storage in Cirebonquarry on each ecosystem types. In deep, it will give information which ecosystem and carbon pool that contributes thehighest carbon stock. The carbon stock calculating methods in above-ground was based on RaCSA (Rapid Carbon StockAppraisal) methods. Based on the observation, there are three ecosystem types in Cirebon Quarry i.e. Opened Area, ThickBushes and Secondary Forest. The result showed that Secondary forest had the highest total C-stock which was 87.18 t Cha-1, while the C-stock on Thick Bushes and Opened Area were 42.95 and 17.92 respectively. The total C stock inbiodiversity conservation area of Cirebon Quarry was 148.05 t C ha-1 comprises 48% of C plant biomass and 52% of Csoil.Key words: carbon stock, Cirebon quarry, limestone area